Is Reliable Information Technology Important For Supporting Work-From-Home Practices in Mining Companies After the Pandemic? - Winata, Nodi; Fitriani, Sri; Gustari, Mugi; Maharani, Anita (Yayasan Ilomata, 2024)
The goal that is expected to be achieved in this research is to determine the influence of IT reliability in supporting WFH for work-life balance, employee performance and cost reduction in mining companies. There has not been much research on WFH practices with reliable IT support in mining companies, where mining companies generally use long working hours for their employees to be fully present at the mining site. The population in this research are employees of mining companies whose mining locations are spread across several places and exploitation activities are carried out entirely by contractors. The research method is descriptive with a quantitative approach. Based on this research, it was found that IT reliability in supporting WFH has a significant impact on work-life balance and cost reduction for employees. However, on the other hand, it was also found that the presence of IT in supporting WFH did not significantly influence employee performance and work-life balance was not found to be able to mediate employee performance.